"To the very limits of our strength?": International interests and domestic concerns in Canadian immigration policy, 1945-1948. - Hartman, David B. (University of Ottawa (Canada), 1996)
This thesis is structured around international interests and domestic concerns as two central issues in the making of Canadian postwar immigration policy from 1945-1948. During the early post World War II period, the Department of External Affairs sought to strike a balance between these issues by integrating a greater consideration of international events into the formulation of Canadian immigration policy. The significant influence that the department had with the government helped to introduce a new dimension of active liberal internationalism and a keener sense of global responsibility and commitment into the national debate on immigration. Nevertheless, despite these efforts, the formulation and administration of Canada's immigration policy in the immediate postwar years was dominated by considerations of national self-interest, domestic politics and the national economy.
Keywords: History, Canadian.